The protective role of intracellular glutathione in Saccharomyces cerevisiae during lignocellulosic ethanol production - Raghavendran, Vijayendran (AMB Express, 2020)
To enhance the competitiveness of industrial lignocellulose ethanol production, robust enzymes and cell factories are vital. Lignocellulose derived streams contain a cocktail of inhibitors that drain the cell of its redox power and ATP, leading to a decrease in overall ethanol productivity. Many studies have attempted to address this issue, and we have shown that increasing the glutathione (GSH) content in yeasts confers tolerance towards lignocellulose inhibitors, subsequently increasing the ethanol titres. However, GSH levels in yeast are limited by feedback inhibition of GSH biosynthesis. Multidomain and dual functional enzymes exist in several bacterial genera and they catalyse the GSH biosynthesis in a single step without the feedback inhibition. To test if even higher intracellular glutathione levels could be achieved and if this might lead to increased tolerance, we overexpressed the genes from two bacterial genera and assessed the recombinants in simultaneous saccharification and fermentation (SSF) with steam pretreated spruce hydrolysate containing 10% solids. Although overexpressing the heterologous genes led to a sixfold increase in maximum glutathione content (18 µmol g(drycellmass)(−1)) compared to the control strain, this only led to a threefold increase in final ethanol titres (8.5 g L(− 1)). As our work does not conclusively indicate the cause-effect of increased GSH levels towards ethanol titres, we cautiously conclude that there is a limit to cellular fitness that could be accomplished via increased levels of glutathione.